Felicity Condition of Expressive Speech Act Uttered by Public Figures in Covid-19 News - Hadiati, Chusni; Yulianita, Nadia Gitya; Muttaqin, Usep (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract.  This research aims to identify the expressive speech act and its felicity condition uttered by high-profile figures. It specifically attempts to recognize the types of expressive speech act, the intended meaning of those expressive speech act types, and their felicity conditions. The qualitative method was applied to accomplish those study objectives. The data were high-profile figures’ utterances collected from covid-19 related news on an online news site (https://www.merdeka.com/).  This research focuses on the expressive speech acts since they are also known as evaluative speech acts. Moreover, analyzing expressive speech acts uttered by public figures in covid-19 related news may give insight on how the Indonesia’s government manage covid-19 cases. The results confirm that the utterances taken from that site fulfilled some types of expressive speech act, namely praising, thanking, deploring, lamenting, congratulating, and flattering. The intended meaning of those types of expressive speech act are determined by interpreting the speakers’ intention based on the context. Furthermore, the felicity condition of each expressive speech act type is discovered by conducting four formulas, which are preparatory condition, propositional content, sincerity condition, and essential condition. These formulas determine the validity of the utterances. Thus, people reading the news can refer that the utterances are not hoaxes.   Keywords: Expressive Speech Act, Felicity Condition, Covid-19, Public Figures